Factor Analysis Of Working Environment Factors, Worker Awareness, Top Management, Worker Communication, Regulations and Procedures(K3), And Availability of Signs (K3) to The Occupational Health And Safety (K3) Implementation At PT. Primary Mirasindo - Dian Mulyaningtyas; Nadiya Pranela; Mia Syafrina (Journal of Applied Business Administration, 2023)
This study aims to determine the analysis of work environment factors, worker awareness, work motivation, top management, worker communication, K3 rules and procedures, and the availability of K3 signs that significantly affect Occupational Health and Safety at PT. Mirasindo Perdana partially and simultaneously. The sample in this study used random sampling, so that the results obtained were 134 respondents from employees of PT. Mirasindo Perdana, the data collection technique used is through a questionnaire. This study uses factor analysis and multiple linear regression analysis with the help of computer software for SPSS version 20 statistics. work (X3), top management (X4), worker communication (X5), K3 rules and procedures (X6), and the availability of K3 signs (X7) have a positive and significant simultaneous effect on Occupational Health and Safety. while those that partially represent independent variables or other factors are top management (X4), K3 rules and procedures (X6), and the availability of K3 signs (X7). It can be seen that top management (X4), K3 regulations and procedures (X6), and the availability of K3 signs (X7) have a positive and significant impact on Occupational Health and Safety at PT. Mirasindo Perdana.